1998
DOI: 10.1210/jc.83.11.3984
|View full text |Cite
|
Sign up to set email alerts
|

Premature Response to Luteinizing Hormone of Granulosa Cells from Anovulatory Women with Polycystic Ovary Syndrome: Relevance to Mechanism of Anovulation

Abstract: Polycystic ovary syndrome is the most common cause of anovulatory infertility. Anovulation in polycystic ovary syndrome is characterized by the failure of selection of a dominant follicle with arrest of follicle development at the 5-10 mm stage. In an attempt to elucidate the mechanism of anovulation associated with this disorder we have investigated at what follicle size human granulosa cells from normal and polycystic ovaries respond to LH. Granulosa cells were isolated from individual follicles from unstimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
153
0
16

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(177 citation statements)
references
References 0 publications
8
153
0
16
Order By: Relevance
“…As opposed to normal women, where inhibin B production by granulosa cells in the early follicular phase is under the control of FSH but not LH, theca interstitial cells around small antral follicles in PCOS patients might respond with an increased α-subunit expression to elevated LH levels, supplying granulosa cells with an increased amount of this subunit, which would result in an elevated secretion of inhibin B by granulosa cells. Furthermore, premature sensitivity of granulosa cells from small antral follicles to LH has been reported in PCOS [31], thus LH might also stimulate inhibin B production directly in granulosa cells. In contrast to these findings and theories, several studies demonstrated reduced expression of the α-subunit in PCOS granulosa cells, which, possibly regulated by elevated LH levels, might be responsible for decreased inhibin A and B concentrations in follicular fluid [32,33].…”
Section: Discussionmentioning
confidence: 98%
“…As opposed to normal women, where inhibin B production by granulosa cells in the early follicular phase is under the control of FSH but not LH, theca interstitial cells around small antral follicles in PCOS patients might respond with an increased α-subunit expression to elevated LH levels, supplying granulosa cells with an increased amount of this subunit, which would result in an elevated secretion of inhibin B by granulosa cells. Furthermore, premature sensitivity of granulosa cells from small antral follicles to LH has been reported in PCOS [31], thus LH might also stimulate inhibin B production directly in granulosa cells. In contrast to these findings and theories, several studies demonstrated reduced expression of the α-subunit in PCOS granulosa cells, which, possibly regulated by elevated LH levels, might be responsible for decreased inhibin A and B concentrations in follicular fluid [32,33].…”
Section: Discussionmentioning
confidence: 98%
“…We provide evidence here that overexpression of functional LHCGR in GCs of PCOS is likely to be part of the mechanism of OHSS. Moreover, previous studies suggested that LHCGR may be expressed prematurely in women with PCOS (Jakimiuk et al, 2001, Willis et al, 1998. Interestingly, a number of genes involved in gonadotrophic response, steroidogenesis and water permeability e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have suggested that LHCGR, which is critical for ovulation, may be induced prematurely in women with PCOS (Jakimiuk et al, 2001, Willis et al, 1998. Despite a plethora of studies on clinical, metabolic, genetic and evolutionary factors in PCOS (Gorry et al, 2006, BenShlomo and Younis, 2014, Corbett and Morin-Papunen, 2013, Williams et al, 2013, only few studies have advanced our understanding of the physiopathology of this disorder.…”
Section: Introductionmentioning
confidence: 99%
“…during the mid follicular phase [13]. Interestingly, it has been shown that in ovulatory women with or without polycystic ovaries, granulosa cells responded to LH once follicles reached 9.5-10 mm, whereas in anovulatory patients with polycystic ovaries they responded to LH in follicles smaller than 4 mm [39]. LHR expression is further induced by FSH stimulation before oocyte maturation [10].…”
Section: Introductionmentioning
confidence: 99%